A cell population that strongly expresses the CB1 cannabinoid receptor in the ependyma of the rat spinal cord. Issue 1 (22nd November 2012) - Garcia‐Ovejero, Daniel; Arevalo‐Martin, Angel; Paniagua‐Torija, Beatriz; Sierra‐Palomares, Yolanda; Molina‐Holgado, Eduardo
Abstract The cells surrounding the central canal of the spinal cord are a source of stem/precursor cells that may give rise to neurons, astrocytes, or oligodendrocytes. However, they are a heterogeneous population that remains poorly understood. Here we describe a subpopulation characterized by their strong expression of the CB1 cannabinoid receptor, oval/round soma, apical nucleus, a variable number of cilia (0, 1, or 2), and the presence of a single short and occasionally ramified basal process. These cells are mainly located in the lateral and dorsal central canal throughout the spinal cord. These CB 1(HIGH)<inline-graphic xlink:href="ark:/27927/pgg1dk2pw1g" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> cells are closely related to the basal lamina labyrinths or fractones derived from subependymal microglia. In addition, CB 1(HIGH)<inline-graphic xlink:href="ark:/27927/pgg1dk2pvzv" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> cells express some stem/precursor cell markers, including vimentin, nestin, Sox2, Sox9, and GLAST, but not others such as CD15 or GFAP. In addition, this cell population does not proliferate in the intact adult spinal cord, although up to 50% of these cells express the proliferation marker Ki67 in newly born rats or after a spinal cord contusion. The present findings contribute to our understanding of the spinal cord central canal structure and reveal the targets for endocannabinoids inside this neurogenic niche. J. Comp. Neurol. 521:233–251, 2013. © 2012 Wiley Periodicals, Inc.